Independent introductions and nosocomial transmission of Candida auris in Saudi Arabia ─ a genomic epidemiological study of an outbreak from a hospital in Riyadh - Qingtian Guan; Faisal Alasmari; Chang Li; Sara Mfarrej; Mahmoud Mukahal; Stefan T. Arold; Talal S. AlMutairi; Arnab Pain (Microbiology Spectrum)
ABSTRACT Candida auris, a pathogenic yeast responsible for global healthcare-associated outbreaks, was involved in a significant outbreak at King Fahad Medical City (KFMC) in Riyadh, affecting 20 patients from August 2018 to May 2019. Our study analyzed 23 C. auris isolates from these patients, utilizing whole genome sequencing, single-nucleotide polymorphism (SNP) analysis, phylogenetic analysis, and transmission network construction. We identified four phylogeographic clades in Saudi Arabia, with two present among the KFMC isolates. The transmission network predominantly displayed two star-like patterns, indicative of super-spreader events. Resistance to various azoles was common, and one isolate was resistant to 5-flucytosine, linked to specific mutations in the ERG11 and CIT1 genes. High genetic similarity of the isolates suggested a nosocomial origin of the KFMC outbreak. The distribution of phylogeographic clades suggests at least four separate introductions into Saudi Arabia from 2017 to 2019 and two into KFMC, underscoring both direct and nosocomial transmission pathways within the hospital.IMPORTANCECandida auris is an emerging multidrug-resistant yeast that poses a significant threat in healthcare settings worldwide. This study is one of the largest genomic investigations of a Candida auris outbreak in the Middle East, focusing on a hospital in Riyadh, Saudi Arabia. By analyzing the genomes of isolates from 20 patients, we uncovered multiple independent introductions of C. auris into the region, as well as its subsequent spread within a hospital. The findings highlight the complex transmission dynamics and the challenges in controlling this pathogenic yeast in healthcare environments. This research underscores the critical need for robust genomic surveillance and accurate identification methods to prevent and manage C. auris outbreaks, which are increasingly linked to high mortality rates and limited treatment options. The insights gained from this study contribute to our understanding of C. auris transmission and resistance, offering valuable guidance for public health strategies.